A divergent synthesis of 3, 10-dialkylpicenes12. Issue 5 (24th March 2015) - Chen, Xi-Chao; Nishinaga, Shuhei; Okuda, Yasuhiro; Zhao, Jia-Ji; Xu, Jie; Mori, Hiroki; Nishihara, Yasushi
Abstract : A series of 3, 10-dialkylated picenes has been synthesized through sequential Ni-catalyzed alkynylation of a C–O bond, alkylation, and hydrogenation. Abstract : A series of 3, 10-dialkylated picenes has been synthesized from 3, 10-dimethoxypicene through a divergent approach involving Ni-catalyzed alkynylation of a C–O bond, alkylation, and hydrogenation.